Role of Bifidobacterium infantis in the Treatment of Duodenal and Colon Inflammation in Induced Ulcerative Colitis - Al-Qayim, Majida; Muhsin Al-Rudaini, Ali; Sezgin, Mehmet; Badr Falih, Inam (The Iraqi Journal of Veterinary Medicine, 2022)
This study aimed to investigate the potential protective role of Bifidobacterium (B.) infantis in alleviating ‎‎induced duodenal and colon inflammation associated with ulcerative colitis (UC). Female albino Wister rats ‎‎(n=24) ‎were randomized into four experimental groups: Control Negative, acetic acid-induced colitis (AA colitis), ‎B. infantis-treated (Bifido), orally gavaged with 1 mL of reference strain ‎B. infantis at 108 CFU/mL for four weeks prior to the induction of colitis,‎ and Bifido+AA ‎colitis. Colitis was induced via ‎intrarectal administration of 4% AA solution‎. Seven days post-colitis induction, blood samples were ‎obtained to assess protein levels, and histopathological evaluations were conducted on duodenal and ‎colon tissues. ‎Additionally, immunohistochemical assessments for B-cell lymphoma 2‎ (Bcl-2) in colon and ‎myeloperoxidase (MPO) in duodenum ‎sections were performed‎. Results revealed that B. infantis treatment significantly elevated serum albumin and total ‎protein levels in the Bifido and Bifido+AA colitis groups, approximating those in the Control Negative group. Histopathological and morphological changes of duodenum in AA colitis revealed ulceration of the mucosal epithelium, submucosal inflammatory cellular infiltration, tissue depression resulting in villus atrophy, and crypt hyperplasia. Additionally, ‎colonic crypt gland atrophy and goblet cells depletion were observed. Most of these changes were ameliorated in the Bifido and Bifido+AA colitis groups. Immunohistochemical analysis displayed marked immunopositivity ‎ of Bcl-2 in colon and MPO in duodenum sections of the Bifido and Bifido+AA colitis groups, indicating the antiapoptotic and anti-inflammatory roles of B. infantis. This study demonstrates that B. infantis exerts a protective effect against AA-induced UC by normalizing serum protein levels, ameliorating histopathological alterations, and ‎modulating apoptotic and inflammatory markers. These findings underscore B. infantis as a ‎promising therapeutic agent for UC and warrant further research to elucidate the underlying ‎molecular mechanisms.